Pesantren-Based Madrasah Management Model at MTs Al Falah Jatirokeh Brebes - Fithri, Askini Ainul; Jamalullel, Jamalullel; Nurfaizah, Nurfaizah; Yani, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article discusses the management of Islamic boarding school-based madrasa at MTs Al Falah Jatirokeh Brebes, which aims to integrate religious education with the formal education system in order to create graduates who are competent in both academic and moral aspects. In facing the challenges of modern education, this research wants to explore the management model applied in this madrasa. The research method used is qualitative research with a field approach, which involves interviews, observation and document analysis to collect in-depth data regarding madrasa management practices. The research results show that the Islamic boarding school-based madrasa management at MTs Al Falah Jatirokeh Brebes has succeeded in integrating the Islamic and general education curriculum, with an emphasis on active learning through interactive methodology. Apart from that, the implementation of digital classes has improved the quality of education and attracted students' interest in learning. However, the challenge of social stigma towards Islamic boarding schools is still an obstacle that needs to be overcome so that community support for these madrasas can increase.